Assessment of contact involvements and scrums in international rugby union match-play using video analysis and microsensor technology methods - Menzies, F. A.; Walsh, J.; Boyd, A. J.; Turner, A. P. (Journal of Sports Sciences, 2023)
This study sought to assess the validity of contact involvement (CI) detection using microsensor technology (MST, Catapult Vector) within the context of a Tier One national rugby union (RU) squad, consisting of 44 players. Sensitivity of MST units to detect CI and scrums was assessed in eight test matches, by comparison with match data obtained by video analysis. This paper is the first to assess the sensitivity of MST to the full range of skilled CI which occur in RU, including evaluating "non-performance" collisions, such as incidental collisions or foul play. Sensitivity to tackles made (52.9-84.9%) and ruck hits (53.3-87.2%) was lower than previous research, although ball carries (71.9-93.5%) showed broadly similar sensitivity to established results. The sensitivity of the MST to detect scrums was substantially lower than previous findings, with large positional variation evident (51.4-91.5%). Further refinement of MST software should be considered in order to facilitate valid monitoring of RU performance and injury risk. An additional finding was that video analysis generally demonstrated satisfactory intrarater reliability. This result supports the use of video analysis as a reliable method of assessing RU performance, including CI.